Satirical representation of social and political issues in Nigerian political cartoons - Sani, Iro (2012)
The attainment of democracy in Nigeria has witnessed a dramatic increase of newspaper cartoons emphasizing the role played by political cartoons in constructing political commentary. This study examined the satirical representation of social and political issues in Nigerian political cartoons. The study used genre, agenda setting and perceptual theories as its theoretical framework to provide explanation on how the Nigerian media via the political cartoons genre capture and reinforce social realities. Using semiotic and linguistic analyses, a sample of 1000 political cartoons published in the two most widely read Nigerian newspapers and one magazine during the period 2007-2010 was extracted and analyzed. The results indicated the predominant themes that emerged from the satirical representation of social and political issues in Nigerian political cartoons during the period: democratic governance, corruption, economy, standard of living, foreign policy, security and lack of leadership. The findings also showed how verbal and visual elements combine together to construct meaningful messages using devices including metaphors, metonymy, myths and syntagmatic relations. Further, Nigerian political cartoons express group ideology. The findings also showed that the cartoonists employed two specific tones for depicting satirical representation, with the laughing satirical tone indicating reformative mode being the more frequent satirical tone used. Finally, the study has implications for further research with regard to the use of images and words to communicate important issues in society.